Properties of electromagnetic waves that propagate along the left-hand material slab - Azarenkov, N.A.; Akimov, Yu.A.; Galaydych, V.K.; Olefir, V.P.; Sporov, A.E. (Вопросы атомной науки и техники, 2009)
This report is devoted to the investigation of the dispersion and the spatial distribution of the electromagnetic field of the surface type waves that propagate along the planar waveguide structure. This structure consists of the left-handed material slab, bounded by the semi-infinite regions of ordinary dielectric with constant permittivity and permeability. The wave considered propagates along the interface between left and right handed materials. The obtained results can be useful for the future image processing applications.